TANTANGAN PROFESI HUMAN RESOURCES PADA ERA DISRUPSI 4.0 - Agustina, Ismaya Dwi (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
The Covid-19 outbreak has caused several impacts ranging from the education sector, the economic sector, the political sector to the employment sector. Human Resources are one of the most important assets in organizational progress so they need to be managed to achieve organizational goals. In the Disruption 4.0 era, investment in development and strengthening the quality of human resources will have a major impact on accelerating long-term development. Disruption is basically an innovation that replaces a series of old systems with a new system that is innovative and efficient. In the era of disruption 4.0, the role and challenges of the human resources profession have also increased. Of course, it doesn't just focus on administration and management of human resources, the human resources profession must be at the forefront of the company's digital transformation